Comparison of Pulping Studies of Australian Seed Routed Eucalyptus Plantations in Amlai Region - Khare, Alok; Mishra, K. N.; Bhargava, G. G.; Pande, M. C.; Thusu, N. K. (Indian Forester, 2007)
E. camaldulensis, E. urophylla, E. saligna and E. tereticornis plantations in Amlai region of Madhya Pradesh through seed route were raised from Australian seeds procured from Australian Tree Seeds Centre CSIRO Division. MAI achieved after seven years of growth was maximum in E. saligna followed by E. camaldulensis, E. urophylla and E. tereticornis. E. urophylla and E. saligna wood of seven years of age need 2.0% more alkali than E. camadulensis and 1.0% than E. tereticornis in cooking operation to produce bleachable grade pulp. E. saligna is better in MAI and bleached pulp strength properties than other Eucalyptus species. E. camadulensis was observed to be inferior in respect of unbleached and bleached pulp yield and various physical strength properties than other Eucalyptus species.